1993
DOI: 10.1007/bf02451907
|View full text |Cite
|
Sign up to set email alerts
|

Pineal regulation of circadian rhythms of 2-deoxy[14C]glucose uptake and 2[125I]iodomelatonin binding in the visual system of the house sparrow,Passer domesticus

Abstract: Abstract. The pineal gland and its hormone melatonin are crucial for the generation of circadian rhythms in several species of passerine birds. The sites and mechanisms by which they influence avian behavior are therefore of particular interest. Recent research employing several brain imaging techniques has indicated that the sites of melatonin action within the avian brain are widespread within the 4 major visual pathways. In this study, we have investigated whether the avian homologue of the mammalian suprac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 47 publications
(67 reference statements)
3
35
0
Order By: Relevance
“…Furthermore, in the absence of HCRT signaling, the downstream melatonin pathway and/or circuit could be up-regulated to compensate for the decrease of melatonin production, thus explaining the hypersensitivity to melatonin of hcrtrϪ/Ϫ fish. Such a regulatory loop has been previously reported in mammals and birds where melatonin receptor numbers increased after pinealectomy (24). Moreover, interestingly, HCRT fiber and hcrtr mRNA distributions (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, in the absence of HCRT signaling, the downstream melatonin pathway and/or circuit could be up-regulated to compensate for the decrease of melatonin production, thus explaining the hypersensitivity to melatonin of hcrtrϪ/Ϫ fish. Such a regulatory loop has been previously reported in mammals and birds where melatonin receptor numbers increased after pinealectomy (24). Moreover, interestingly, HCRT fiber and hcrtr mRNA distributions (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, hcrtrϪ/Ϫ and wild-type siblings showed no differences upon exposure to the other hypnotics (Fig. S3), demonstrating a specific hypersensitivity to melatonin and suggesting, in this mutant, an up-regulation of the actors downstream of melatonin, which might reflect a reduction of endogenous melatonin signaling (24).…”
Section: Hcrtr؊/؊ Larval and Adult Mutants Are Hypersensitive To The mentioning
confidence: 94%
“…This idea is supported further by the fact that pinealectomized house sparrows can entrain to skeleton photoperiods and choose an appropriate phase with the remnants of their circadian systems (Takahashi and Menaker 1982a). Recently, we have asked whether the circadian rhythm of 2DG uptake within the vSCN (Cassone 1988) and of IMEL binding within the visual system are abolished by pinealectomy (Lu and Cassone 1993). The data indicated that both 2DG uptake within the vSCN and IMEL binding in the vSCN and several other retinorecipient and integrative visual structures are expressed rhythmically in DD for at least 10 circadian cycles in intact sparrows.…”
Section: Introductionmentioning
confidence: 92%
“…First, specific, high affinity receptor binding as revealed by in vitro binding of the melatonin agonist 2-[125I]iodomelatonin (IMEL) and autoradiography is present in the retinorecipent and integrative structures of the circadian (vSCN), tectofugal (TeO, Rt E), thalamofugal (GLv, DL, LA) and accessory optic (EM, EW, OM) visual pathways in many species of birds Stehle 1990;Kelm and Cassone 1990;Siuciak et al 1991;Brooks and Cassone 1992;Cozzi et al 1993) including the house sparrow (Cassone and Brooks 1991). This binding is rhythmic with the highest binding during late subjective day and early subjective night Lu and Cassone 1993). Second, uptake of the metabolic marker 2-deoxy[laC]glucose (2DG) is inhibited by administration of 10 gg/kg exogenous melatonin in circadian and visual structures exhibiting specific IMEL binding but not in structures devoid of binding (Cassone and Brooks 1991).…”
Section: Introductionmentioning
confidence: 97%
“…The exact location of the avian homologue to the mammalian SCN has proven difficult to identify (Dawson, King, Bentley, & Ball, 2001). Some experiments have implicated the medial SCN as the hypothalamic region for the avian circadian oscillator (Simpson & Follett, 1981;Yoshimura, Yasuo, Suzuki, Makino, Yokota, & Ebihara, 2001) whereas other studies point to the more lateral, visual SCN (Lu & Cassone, 1993). Ball & Balthazart (2003) asserted that recent work examining clock gene expression (Yasuo, Watanabe, Okabayashi, Ebihara, & Yoshimura, 2003) demonstrates definitively that the medial hypothalamus is the site of photoperiodic time measurement in birds.…”
mentioning
confidence: 98%